THE INFLUENCE OF THE STRATEGIC PARTNERSHIP OF STATE UNIVERSITIES AND BUSINESS ON THE INVESTMENT ATTRACTIVENESS OF A REGION - IRINA MOROZOVA; ELENA POPKOVA (Revista Galega de Economía, 2015)
The article reveals the essence of the mechanism of regional investment attractiveness escalation through the establishing of sustainable strategic partnership of state universities and local business. The author proves the effect of positive impact which appears as a result of quantity changes in local human capital, and the consequences following such changes are also described.